Seismic behavior of asymmetric RC wall buildings Principles and new deformation-based design method. - Sommer, Alois
The seismic design of multi-story buildings asymmetric in plan yet regular in elevation and stiffened with ductile RC structural walls is addressed. A realistic modeling of the non-linear ductile behavior of the RC walls is considered in combination with the characteristics of the dynamic torsional response of asymmetric buildings. Design criteria such as the determination of the system ductility, taking into account the location and ductility demand of the RC walls, the story-drift demand at the softer (most displaced) edge of the building under the design earthquake, the allowable ductility (ultimate limit state) and the allowable story drift (performance goals) are discussed. The definition of an eccentricity of the earthquake-equivalent lateral force is proposed and used to determine the effective displacement profile of the building yet not the strength distribution under the design earthquake. Furthermore, an appropriate procedure is proposed to calculate the fundamental frequency and the earthquake equivalent lateral force. A new deformation based seismic design method taking into account the characteristics of the dynamic torsional response, the ductility of the RC walls, the system ductility and the story drift at the softer (most displaced) edge of the building is presented and illustrated with an example of seismic design of a multi story asymmetric RC wall building.
Keywords: Dynamic torsional response; Ductile behavior; Asymmetric regular buildings; RC structural walls; Performance based design; Ductility demand